2013
DOI: 10.1073/pnas.1311055110
|View full text |Cite
|
Sign up to set email alerts
|

TP53 suppression promotes erythropoiesis in del(5q) MDS, suggesting a targeted therapeutic strategy in lenalidomide-resistant patients

Abstract: Stabilization of p53 in erythroid precursors in response to nucleosomal stress underlies the hypoplastic anemia in myelodysplastic syndromes (MDS) with chromosome 5q deletion [del(5q)]. We investigated whether cenersen, a clinically active 20-mer antisense oligonucleotide complementary to TP53 exon10, could suppress p53 expression and restore erythropoiesis in del(5q) MDS. Cenersen treatment of ribosomal protein S-14-deficient erythroblasts significantly reduced cellular p53 and p53-up-regulated modulator of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…In keeping with this model, resistance to LEN has been shown to be associated with restoration of P53 accumulation, and ACCEPTED MANUSCRIPT inhibition of TP53 expression by an antisense oligonucleotide modestly enhances del(5q) erythropoiesis 126 . Finally, sub-clonal TP53 mutations are associated to lower rates of cytogenetic responses to LEN, though they do not influence the restoration of erythropoiesis 127 .…”
Section: Len In 5q-syndromesmentioning
confidence: 71%
“…In keeping with this model, resistance to LEN has been shown to be associated with restoration of P53 accumulation, and ACCEPTED MANUSCRIPT inhibition of TP53 expression by an antisense oligonucleotide modestly enhances del(5q) erythropoiesis 126 . Finally, sub-clonal TP53 mutations are associated to lower rates of cytogenetic responses to LEN, though they do not influence the restoration of erythropoiesis 127 .…”
Section: Len In 5q-syndromesmentioning
confidence: 71%
“…Note: *frequent mutation site. [58,121]. In Wu's study, U2AF1 mutation was found to be an independent poor-risk factor for OS in all patients (P = 0.030) and could predict a shorter time-to-leukemia transformation in younger patients (P = 0.020), particularly in lower-risk MDS patients [151].…”
Section: U2af1/u2af35mentioning
confidence: 91%
“…Cenersen, an antisense oligonucleotide complementary to TP53, suppresses mutant p53 expression and restores impaired erythropoiesis in patients with del(5q) MDS [121].…”
Section: Tp53mentioning
confidence: 99%
“…Suppression of p53 reduces apoptosis and restores erythropoiesis in del(5q) MDS progenitors. Specifically, dexamethasone, a glucocorticoid receptor‐dependent p53 antagonist, restored transfusion independence in 5 out of 8 del(5q) MDS patients with acquired drug resistance . Cenersen, a clinically active 20‐mer antisense oligonucleotide complementary to TP53 exon 10, is another treatment that has been shown to reduce apoptosis and restore erythropoiesis in RPS14 deficient erythroblasts by significantly reducing cellular p53 …”
Section: Tp53 Mutation and Disease Progressionmentioning
confidence: 99%
“…Specifically, dexamethasone, a glucocorticoid receptor-dependent p53 antagonist, restored transfusion independence in 5 out of 8 del(5q) MDS patients with acquired drug resistance. 50 Cenersen, a clinically active 20-mer antisense oligonucleotide complementary to TP53 exon 10, is another treatment that has been shown to reduce apoptosis and restore erythropoiesis in RPS14 deficient erythroblasts by significantly reducing cellular p53. 50 The presence of a TP53 mutation has been associated with resistance to lenalidomide, as well as inferior prognosis compared to patients with wild-type TP53.…”
Section: Tp53 Mutati On and D Is E A S E Prog Re Ss I Onmentioning
confidence: 99%